In vitro and in vivo study of fucoxanthin bioavailability from nanoemulsion-based delivery systems: Impact of lipid carrier type - Salvia-Trujillo, L.; Sun, Q.; Urn, B. H.; Park, Y.; McClements, D. J. (ELSEVIER SCIENCE BV, 2015)
The impact of carrier oil type on the functionality of a lipophilic nutraceutical (fucoxanthin) encapsulated within nanoemulsions was investigated. Three carrier oils were investigated: long chain triacylglycerols (LCT); medium chain triacylglycerols (MCT); and indigestible oil (orange/mineral oil). Nanoemulsions containing LCT and MCT were completely digested under simulated gastrointestinal conditions, whereas those containing indigestible oil were not digested. Fucoxanthin solubility in mixed micelles formed by in vitro digestion decreased in the following order: LCT > MCT > indigestible oil. Animal feeding studies revealed that fucoxanthin was absorbed into the intestinal epithelial cells in the same order as observed for the in vitro solubility. However, the concentration of fucoxanthin in the serum of the rats was similar for all carrier oils. The present work highlights the importance of contrasting in vitro and in vivo experiments to assess the biological fate of functional ingredients incorporated in emulsion-based delivery systems. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: BETA-CAROTENE BIOACCESSIBILITY; MEDIUM-CHAIN TRIGLYCERIDES; DIGESTION MODELS; INTESTINAL-ABSORPTION; ORAL BIOAVAILABILITY; DIETARY CAROTENOIDS; FATTY-ACIDS; PORTAL-VEIN; OIL; EMULSIONS